La falta de utilización del equipo técnico de la Unidad de Familia para resolver el régimen de visitas cerrado a favor del alimentante. - Shiguango Tanguila, Elisa Mabel (2024)
The aim of this research work is to carry out a legal analysis of the lack of use of the technical team of the Family Unit to resolve the Closed Regime in favour of the provider; the importance of carrying out a study from the doctrine, jurisprudence, the law and the development of the case in the judicial units, which are important to establish the possible affectations that can occur in the rights of both the providers and the children and adolescents who have full rights to share with their parents for their integral development and wellbeing. Judicial decisions without technical support have consequences for all those involved, fundamentally for the minors, which is why it is necessary to investigate how much legal weight the reports of the Technical Units of the Family, Women, Children and Adolescents Units have at the time of the decision, given that in the majority of cases the judges adhere strictly to the content of the law; for this reason, unconstitutional actions have even been filed against the content of the Organic Code for Children and Adolescents. It should be known that the objective of the closed visiting regime is to protect the physical and psychological integrity of the child; That is to say, to avoid any type of violence by the parent, which is why this should be verified by the use of the Technical Team of the Family, Women, Children and Adolescents Unit, so that the use of the technical team to assign the closed visiting regime to the requesting parent will contribute to the affective, physical and emotional development, and above all to avoid possible violations of a comprehensive right of minors, as stated in the Constitution of Ecuador. As this is a descriptive research, descriptive methods were used in order to define, 4 catalogue, classify or characterise the object of study; as this research is a legal topic, nomothetic and ideographic methods were used. The methodology of qualitative type, with the dogmatic and interpretative method of the constitutional and legal norm, because through these methods an answer is offered to the treated problem, from what creates the best possible reconstruction by the legal material that we have at our disposal, in addition the facts or social phenomena studied in this work are measurable and quantifiable, to measure and establish causal relationships between the variables, to explain the problem of study and the current reality. KEY WORDS: visiting rights, rights, technical team, integral development.